Isotopic characterization of water masses in the Southeast Pacific region: Paleoceanography implications - Dharma Reyes-Macaya; Babette A A Hoogakker; Gema Martínez-Méndez; Pedro Llanillo; Mahyar Mohtadi; Patricia Grasse; Alan C Mix; Melanie J Leng; Ulrich Struck; Daniel C McCorkle; Macarena Troncoso; Eugenia Gayo; et al. (PANGAEA, 2022)
This study aims at measuring and understanding the characteristics of the Southeast Pacific (SEP) water masses using stable isotopes of oxygen, deuterium and dissolved inorganic carbon along with other parameters such as temperature, salinity and oxygen, and nutrient concentrations. The data set summarizes new measurements and published data from 1992 to 2018 bellow 55 m water depth from the following expeditions: TAITAO, SO-261, SO-245, 316N138-3 (P06), 49NZ20030909 (P06), 318M20100105 (P06), LOWPHOX 1, RR9702a, SO-102, SO-211, Station18-Udec, CIMAR-21, Crio1812, 316N138_12 (P19), M93. In all expeditions, Seabird-CTDs attached to Rosettes of Niskin bottles were used to measure conductivity, temperature, pressure and oxygen. Carbon, oxygen, deuterium and nutrient samples were siphoned from Niskin bottles into 4-15 mL plastic vials, measured onboard or stored at -20 C for later measurements. In the paper, the data is separated into coastal (71-78 °W) and oceanic section (82-98 °W). However, we incorporate in the data reservoir as well an intermediate section (79-81 °W). Several paleoceanographic studies in marine sediments records from the Peru-Chile Continental Margin compare their results with oceanic data, due to insufficient hydrological characterization of the coastal section. The new data provide here were collected near the sediment core sites in the region, giving the chance to begin used as a present-day hydrological analogue for paleoenvironmental reconstructions.